2022
DOI: 10.1186/s12935-022-02648-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory function of DNA methylation mediated lncRNAs in gastric cancer

Abstract: As one of the most common malignancies worldwide, gastric cancer contributes to cancer death with a high mortality rate partly responsible for its out-of-control progression as well as limited diagnosis. DNA methylation, one of the epigenetic events, plays an essential role in the carcinogenesis of many cancers, including gastric cancer. Long non-coding RNAs have emerged as the significant factors in the cancer progression functioned as the oncogene genes, the suppressor genes and regulators of signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 107 publications
(112 reference statements)
0
14
0
Order By: Relevance
“…29 LncRNAs also play crucial roles in GC progression. 30 It has been shown that lncRNA SNHG3 acts as a tumor-promoting factor in multiple malignancies including GC [31][32][33] but acts as a tumor suppressor in papillary thyroid carcinoma. 34 We herein found that knockdown of METTL3 decreased the m 6 A modification levels of SNHG3, and overexpression of SNHG3 abolished METTL3 knockdownled proliferation inhibition and unveiled poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…29 LncRNAs also play crucial roles in GC progression. 30 It has been shown that lncRNA SNHG3 acts as a tumor-promoting factor in multiple malignancies including GC [31][32][33] but acts as a tumor suppressor in papillary thyroid carcinoma. 34 We herein found that knockdown of METTL3 decreased the m 6 A modification levels of SNHG3, and overexpression of SNHG3 abolished METTL3 knockdownled proliferation inhibition and unveiled poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of VEGF is affected by a number of factors, EGF receptor 2, methylation, transforming growth factor (TGF)-α and β, and TNF-α, among which oxygen tension is the most important for pathological angiogenesis (88,89). Hypoxia can rapidly induce VEGF mRNA expression through hypoxia-inducible factor-1 (HIF-1), thus promoting downstream signal transduction (90).…”
Section: Vegf and Inhibition Of The Vegf Pathway In Nsclcmentioning
confidence: 99%
“…Z-ajoene also facilitates β-catenin degradation by regulating CK1α activity (160). Studies using Z-ajoene for the treatment of gastric cancer suggested that the proliferation of MGC-803 gastric cancer cells was considerably inhibited (161,162). Artemisinin is an active sesquiterpene extracted from Artemisia annua.…”
Section: Pnu-74654 Gb1874 and Inhibitor Of B-catenin And Tcf (Icat) P...mentioning
confidence: 99%